1982
DOI: 10.1161/01.cir.66.1.108
|View full text |Cite
|
Sign up to set email alerts
|

The effects of airway pressure on cardiac function in intact dogs and man.

Abstract: Ventilation with positive end-expiratory pressure (PEEP) is associated with reduced cardiac output, but the mechanisms involved are controversial. Possible explanations include increased intrathoracic pressure, reflex changes in myocardial inotropism, pulmonary vascular obstruction and abnormal ventricular interaction. Three types of conscious canine preparations were developed to examine simultaneously each of these factors during ventilation with PEEP. In addition, similar measurements were obtained in patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
45
0

Year Published

1983
1983
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(48 citation statements)
references
References 23 publications
3
45
0
Order By: Relevance
“…9 Despite some conflicting results,13 the majority of authors on this subject' 2, 9, 14 believe that lung inflation increases the left and reduces the right ventricular stroke output. But, as inflation progresses, left ventricular stroke output decreases secondarily as a result of reduced right ventricular stroke output, which is followed by left ventricular stroke output after a phase lag of 1 In accord with previous studies9 1, 14 the inspiratory reduction in pulmonary arterial flow observed in this study was followed after a phase lag of 2 beats by a reduction in systemic arterial flow, which began at the end of inhalation and was consequently pronounced during exhalation. Thus, reversed pulsus paradoxus FIGURE 7.…”
Section: Resultssupporting
confidence: 92%
“…9 Despite some conflicting results,13 the majority of authors on this subject' 2, 9, 14 believe that lung inflation increases the left and reduces the right ventricular stroke output. But, as inflation progresses, left ventricular stroke output decreases secondarily as a result of reduced right ventricular stroke output, which is followed by left ventricular stroke output after a phase lag of 1 In accord with previous studies9 1, 14 the inspiratory reduction in pulmonary arterial flow observed in this study was followed after a phase lag of 2 beats by a reduction in systemic arterial flow, which began at the end of inhalation and was consequently pronounced during exhalation. Thus, reversed pulsus paradoxus FIGURE 7.…”
Section: Resultssupporting
confidence: 92%
“…Rankin et al (7) examined the mechanical and d@ensional changes that occur in the dog heart during change in Paw and found that increases in Paw decrease preload in the left ventricle which reduces stroke volume. They hypothesized that the reduction in left ventricular preload was due to a decrease in blood flow through the lungs caused by an increase in PVR.…”
Section: Resultsmentioning
confidence: 99%
“…In both ventricles, systolic dimensional shortening correlated with measured stroke volume (figure 2) and regional stroke work correlated with global stroke work (figure 3) before and after ischemia. The mean slope and x intercept of equation 5 relating stroke volume to dimensional shortening and of equation 6 figure 6. Left ventricular developed pressure increased and systolic dimensional shortening decreased at a given end-diastolic length compared with control ( figure 6, A).…”
Section: Resultsmentioning
confidence: 99%